Research into protective properties of electromagnetic screens based on the metal-containing nanostructures - Glyva, Valentin; Kovalenko, Viktoriya; Levchenko, Larisa; Tykhenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2017)
We developed and examined protective properties of the metal polymeric electromagnetic screens. We used metal-containing particles of nano dimensions as a filler in the polymeric matrix. It was established that this provides shielding coefficient of 10 dB at the content of a metal substance of 11–12 %. In this case, reflection coefficients are 0.27–0.30. This is not attainable for the materials based on macro particles. It was found that increasing the dispersion of particles by 2–4 times reduces reflection coefficient by 0.15–0.20. We studied dependence of the electrical-physical properties of material on the content of a metal substance. This allowed us to calculate shielding coefficients and the contribution of protection to them due to the reflection of electromagnetic waves. Micro structural research revealed the uniformity of distribution of metal particles in the body of a polymer matrix. This has provided a possibility to calculate at their low concentrations the required coefficients using the relations for regular metal structures. We have demonstrated experimentally the possibility of fabricating electromagnetic screens of the gradient type in a single layer matrix.